Psychological Well-Being and The Sense of Community Among Displaced (Women) Natural Disaster Survivors - Dicky Pelupessy; S. S. Budi Hartono; Yurik Yang (Jurnal Sains Psikologi, 2020)
The present study investigates the psychological well-being and sense of community of women who were displaced by natural disasters. The study explored the interrelationship between the sense of community (SOC), psychological well-being (PWB), relocation status, and socio-demographic variables. One hundred and ninety women participated in the study (N = 190). Participants completed several self-report measurements (e.g., SCI, PWBS) and were categorized into two groups: those who still dwelled in temporary shelters (n = 96) and those who had permanently relocated (n = 94). There were no significant differences in overall SOC and PWB between the two groups; however, there was a significant difference in personal growth dimension —one out of six PWB dimensions— between those who had permanently relocated and those who still stayed in temporary shelters. The two groups also significantly differed on three SOC dimensions: influence, integration, and fulfillment of needs, and shared emotional connection. Three significant predictors for PWB were found: SOC, marital status, and educational attainment. Overall, SOC was a stronger predictor of PWB than displacement status, or any other socio-demographic variables. Keywords disaster; psychological well-being; internally displaced person; the sense of community; relocation; Indonesia